2020
DOI: 10.1108/ijrdm-01-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumers' showrooming behaviour: a stimulus–organism–response (S-O-R) perspective

Abstract: PurposeThe present piece of research aims at enhancing our understanding of situational and intentional showrooming behaviour. The study further tests and validates a model based on the stimulus–organism–response framework to draw richer insights.Design/methodology/approachThe study adopts a two-phased approach to discover the consumers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 78 publications
(142 reference statements)
7
69
0
Order By: Relevance
“…Such establishment would subsequently affect their response in consumption intention. Notably, the proven model has reflected the frameworks by Arora et al (2020) and Kü hn and Petzer (2018) in identifying consumers' perception (i.e. clothing interest) in the "Organism" role.…”
Section: Theoretical Implicationmentioning
confidence: 91%
See 1 more Smart Citation
“…Such establishment would subsequently affect their response in consumption intention. Notably, the proven model has reflected the frameworks by Arora et al (2020) and Kü hn and Petzer (2018) in identifying consumers' perception (i.e. clothing interest) in the "Organism" role.…”
Section: Theoretical Implicationmentioning
confidence: 91%
“…Nonetheless, multiple studies have often identified one's psychological perspective in the role of the "organism", where it precedes consumption responses, while being directly influenced by external stimulus (Aggarwal and Rahul, 2017;Arora et al, 2020;Kü hn and Petzer, 2018). In this regard, elements including usefulness, information quality, virtual presentations and physical experience are shown to be the stimulus that develop consumers' conception in the forms of trust, satisfaction and perceived value, which in turn, affect their consumption intention.…”
Section: Theory Of Stimulus-organism-responsementioning
confidence: 99%
“…S-O-R framework, used to explain consumer behaviour in this study, is extensively used in the context of retailing. The studies in retailing provide insights for different external environment factors as stimuli ( S ), such as social presence (Wang et al , 2019), website quality (Jiyoung and Lennon, 2013), ambient and design (Chang et al , 2011), brand familiarity (Kaur et al , 2017), showrooming shopping value (Arora et al , 2020) and channel integration (Zhang et al , 2018). The impact of external states on the organism relates to in the inner feelings of the consumers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hence, they utilise the interaction with salespersons and examine products in stores (Schneider & Zielke, 2020). While they enjoy the benefits of searching offline, showroomers finally choose to purchase online due to price‐related benefits such as discounts (Arora, Parida, & Sahney, 2020).…”
Section: Literature Review Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
“…They also exhibit increased cognitive effort towards search (Zha, Li, & Yan, 2013). Previous research shows that consumers who engage in showrooming and webrooming seek more information to reduce pre‐purchase uncertainty and post‐purchase regret (Arora et al, 2020; Flavián et al, 2016). These consumers exhibit high levels of multichannel self‐efficacy (Arora et al, 2017; Arora & Sahney, 2017).…”
Section: Literature Review Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%